Perkembangan Teknologi Sejalan dengan Transformasi Pemahaman Hukum Islam - Suwito Suwito (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2007)
This article discusses the influence of modern science and technology towards certai aspects of islamic law and in the interpretation of legal aspects of al-Qur’an. In the aspect of islamic inheritance, technology of ultrasonography (USG) and DNA test certainly makes difference. The USG can accurately predict the embryo, its sex type, and its number (single, twin, triplest, so on). Likewise, DNA test can assist the identification of fire victims and other unidentified victims. Both technologies can support Islamic inheritance law so that the application of the law become more accurate and simple.